2015
DOI: 10.5194/bg-12-6515-2015
|View full text |Cite
|
Sign up to set email alerts
|

Production regime and associated N cycling in the vicinity of Kerguelen Island, Southern Ocean

Abstract: Abstract. Although the Southern Ocean is considered a high-nutrient, low-chlorophyll (HNLC) area, massive and recurrent blooms are observed over and downstream of the Kerguelen Plateau. This mosaic of blooms is triggered by a higher iron supply resulting from the interaction between the Antarctic Circumpolar Current and the local bathymetry. Net primary production, N uptake (NO − 3 and NH + 4 ), and nitrification rates were measured at eight stations in austral spring 2011 (October-November) during the KEOPS 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 89 publications
6
46
0
Order By: Relevance
“…This latter one is significantly heavier than the Si isotopic composition of the fertilized area measured a few days before (1.99 ± 0.03 ‰, A3-1). As already proposed by Closset et al (2014) and Lasbleiz et al (2014), this suggests that a development of diatoms could have occurred before our sampling, consuming a fraction of the DSi standing stock and increasing the δ 30 Si DSi of surface waters. The same evidence of surface production has also been deduced by Dehairs et al (2015), who observed a slight nitrate depletion and enrichment of δ 15 N-NO − 3 .…”
Section: The Hnlc Reference Stationsupporting
confidence: 72%
See 2 more Smart Citations
“…This latter one is significantly heavier than the Si isotopic composition of the fertilized area measured a few days before (1.99 ± 0.03 ‰, A3-1). As already proposed by Closset et al (2014) and Lasbleiz et al (2014), this suggests that a development of diatoms could have occurred before our sampling, consuming a fraction of the DSi standing stock and increasing the δ 30 Si DSi of surface waters. The same evidence of surface production has also been deduced by Dehairs et al (2015), who observed a slight nitrate depletion and enrichment of δ 15 N-NO − 3 .…”
Section: The Hnlc Reference Stationsupporting
confidence: 72%
“…In the ML, the plateau and HNLC areas exhibited significantly different silicon isotopic composition of both seawater and particles, reflecting the different degrees of Si utilization by diatoms. The HNLC reference station (R2) displayed low chlorophyll a and BSi and very low Si uptake rates, consistent with its iron-depleted condition and the dominance of non-siliceous organisms (see details in Lasbleiz et al, 2014, andClosset et al, 2014). In surface waters of the HNLC area, the concentration of biogenic silica was the lowest measured in the surface during KEOPS-2 (0.30 ± 0.03 µmol L −1 ) and its silicon isotopic composition was low (0.73 ± 0.04 ‰) and similar to A3-1 ( Fig.…”
Section: The Hnlc Reference Stationmentioning
confidence: 67%
See 1 more Smart Citation
“…These phytoplankton groups tend to dominate the autotrophic assemblage later in the growing season (Lochte et al 1993;Dandonneau et al 2004;Barton et al 2013) and are often associated with increased DON (e.g., urea) uptake (Berg et al 1997). This is in contrast to larger diatoms that bloom earlier in the season in response to high NO -3 and silicate inputs (Lochte et al 1993;Alkire et al 2014;Cetinić et al 2015).…”
Section: Implications Of Other N Cycle Processes For Estimates Of Newmentioning
confidence: 99%
“…The region is characterized by some of the largest phytoplankton blooms on Earth, which begin in the spring as the mixed layer shoals and light levels rise. Rapidly growing diatoms typically dominate the spring bloom phytoplankton community, driving high rates of NO -3 uptake and export production (Rynearson et al 2013;Alkire et al 2014;Cetinić et al 2015). As silicate concentrations become limiting, diatom growth slows and smaller phytoplankton such as dinoflagellates and coccolithophores become dominant under the nutrient-deplete conditions characteristic of the late summer (Tarran et al 2001;Dandonneau et al 2004; Barton et al 2013).…”
mentioning
confidence: 99%